Effectiveness of Specific Interventions to Address Stunting in East Java Province in 2023: An Ecological Analysis - Nurul Jannatul Firdausi; Cicik Swi Antika; Agung Dwi Laksono; Waritsah Sukarjiyah (Medical Technology and Public Health Journal, 2026)
The Indonesian Health Survey in 2023 indicates that the prevalence of stunting in Indonesia remains high, at approximately 21.5%. The objective of the present study is to evaluate the efficacy of specific strategies designed to mitigate stunting in East Java Province. The research utilised secondary data, which was gathered ecologically. The study utilised a cross-sectional design, with the prevalence of stunting serving as the dependent variable and eleven distinct interventions as independent variables. The analysis revealed ten strategies that were found to be effective in mitigating stunting. These include anemia screening, iron tablet supplementation for adolescent girls, pregnancy examinations, iron tablet supplementation for pregnant women, supplementary nutrition for pregnant women with chronic energy deficiency, monitoring of toddler growth, exclusive breastfeeding, management of toddlers with nutritional deficiencies, enhancement of immunization coverage, and education for pregnant women and their families, including the promotion of open defecation-free practices. Conversely, the provision of supplemental diets rich in animal protein for toddlers was found to be ineffectual in diminishing the prevalence of stunting. Keywords: Community nutritional status, East Java, Stunting, Specific intervention